Canadian Digestive Health Foundation Public Impact Series. Inflammatory Bowel Disease in Canada: Incidence, Prevalence, and Direct and Indirect Economic Impact. (2010) - Fedorak, Richard N; Wong, Karen; Bridges, Ron
Abstract : The Canadian Digestive Health Foundation initiated a scientific program to assess the incidence, prevalence, mortality and economic impact of digestive disorders across Canada in 2009. The current article presents the updated findings from the study concerning inflammatory bowel diseases – specifically, Crohn's disease and ulcerative colitis.